HIV DNA and Immune Alteration During Successful HAART - Mamadou, Diallo; Yu-Huang, Zheng; Xia, Chen; Bo, He; Hua-Ying, Zhou; Yan, He; Zi, Chen; Qing, Li; Li-Wen, Zheng; Mei, He; Yun-Hai, Yao; Demba, Sarr; et al. (Current HIV Research, 2013)
Background: Highly Active Antiretroviral therapy (HAART) can effectively reduce the viral load to undetectable levels in most HIV-infected patients. However, some patients may still experience impaired immunologic response associated with increased risk of disease progression and death. Objective: The objective of this study was to assess the impact of the HIV DNA load on the immune alteration during successful HAART. Methods: 40 chronic HIV-infected adults initiating HAART were followed for 24 months. The CD4 count, HIV viral load, HIV DNA load, and levels of γ-cytokines IL-2, IL-7 and IL-21 were monitored at baseline (month 0), month 6, 12, 18 and 24 following HAART initiation. Results: The plasma viral load decreased significantly and remained below the detection limits after six months treatment. Likely the HIV DNA load decreased significantly in both cells during 12 months, was undetectable in CD14 monocytes after 18 months, but remained higher in CD3+ T cells during all the follow up. In addition, the HIV DNA load correlated positively between T cells and monocytes in 10 patients who maintained higher HIV DNA load in both cells during 12 months. The CD4 count, IL-2, and IL-21 levels increased significantly during 12 months, whereas IL-7 decreased significantly during 18 months, regardless of the HIV DNA load in T cells. Patients with CD4 count below 200/μl maintained higher HIV DNA load and showed lower increase in CD4 count compared to patients with CD4 count above 200/μl. In patients showing undetectable HIV DNA load in both cells, neither IL-2 nor IL-21 correlated with the CD4 count even after 24 months despite their partial restoration. Conclusion: These results suggest that the HIV DNA load could continuously hamper the CD4 restoration and γ-cytokines functional activities during HAART. This action seemed to be more severe in patients with pre-HAART CD4 count below 200/μl. The CD14 monocytes may contribute to this action as source of T cell infection both before and during HAART.
Keywords: CD14+ monocytes